CORRELATION BETWEEN FATIGUE AND PHYSICAL ACTIVITY IN CHRONIC KIDNEY DISEASE PATIENTS EXPERIENCING HEMODIALYSIS THERAPY - Auliya Wanda Wandita; Surya Putri, Novita; Sugito, Hariadji (Universitas Islam Negeri Alauddin Makassar, 2022)
Chronic kidney disease is a disease that results in a decrease in kidney function so that it cannot filter blood and the remains of the body's metabolism. One of the renal replacement therapies for patients with chronic kidney disease is haemodialysis therapy. Haemodialysis therapy is a kidney replacement therapy using a dialysis machine, this therapy has side effects, one of which is fatigue. This fatigue incident causes the patient's physical activity to be reduced or decreased. Physical activity is a movement or activity that requires energy, one of the factors that causes disruption of physical activity is fatigue. The purpose of this study was to determine the correlation between fatigue and physical activity in patients with chronic kidney disease experiencing haemodialysis therapy. The method used in this study is a correlation study with research design cross sectional with a sample of 88 respondents with using a purposive sampling technique. Data collection using questionnaire FSS (Fatigue Severity Scale) and IPAQ (International Physical Activity Questionnaire). Data analysis using Chi-Square correlation test with SPSS 25 for windows. The results showed that almost all of the respondents experienced fatigue as many as 62 respondents (70.5%) and have a low level of physical activity as many as 47 respondents (53.4%). After statistical analysis, the value of Pearson Chi-Square 51,983 with Asymptotic Significance (2-sided) 0.000 (<0.05) which means that there is a rejection of H0 and acceptance of Ha, so there is a significance. The correlation between fatigue and physical activity in chronic kidney disease patients experiencing haemodialysis therapy at the Blambangan Hospital, Banyuwangi 2022. The level of fatigue experienced by respondents causes troubles in daily activities or physical activity of respondents experiencing therapy haemodialysis.